2021
DOI: 10.1210/clinem/dgab557
|View full text |Cite
|
Sign up to set email alerts
|

Primary Adrenal Insufficiency Due to Bilateral Adrenal Infarction in COVID-19

Abstract: Context Coronavirus disease 2019 (COVID-19) is a proinflammatory and prothrombotic condition, but its impact on adrenal function has not been adequately evaluated. Case report A 46-year-old woman presented with abdominal pain, hypotension, skin hyperpigmentation after COVID-19 infection. The patient had hyponatremia, serum cortisol <1.0 ug/dL, ACTH of 807 pg/mL and aldosterone <3 ng/dL. Computed tomography (CT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…There are at least 12 case studies and nine prospective case series in the literature describing adrenal insufficiency related to COVID-19. These studies reported that adrenal haemorrhages and infarctions might not only occur in severe cases of COVID-19, but also in mild ones 7 . Furthermore, pre-existing adrenal disease or Addison disease can be exacerbated by SARS-CoV-2 infection.…”
Section: Covid-19 and Adrenal Insufficiencymentioning
confidence: 96%
“…There are at least 12 case studies and nine prospective case series in the literature describing adrenal insufficiency related to COVID-19. These studies reported that adrenal haemorrhages and infarctions might not only occur in severe cases of COVID-19, but also in mild ones 7 . Furthermore, pre-existing adrenal disease or Addison disease can be exacerbated by SARS-CoV-2 infection.…”
Section: Covid-19 and Adrenal Insufficiencymentioning
confidence: 96%
“…Incidental adrenal computed tomography findings compatible with adrenal infarction have been reported in 23% of patients with severe COVID-19 [42], the vast majority with bilateral involvement. However, the clinically relevant cases are less frequently reported [43]. Of note, two out of nine clinically relevant cases had positive antiphospholipid antibodies prior to COVID-19 diagnosis, suggesting a previously described link between the antiphospholipid syndrome and the risk of bilateral adrenal infarction in non-COVID-19 patients as a potential mechanism [43][44][45][46].…”
Section: Adrenal Glandmentioning
confidence: 96%
“…However, the clinically relevant cases are less frequently reported [43]. Of note, two out of nine clinically relevant cases had positive antiphospholipid antibodies prior to COVID-19 diagnosis, suggesting a previously described link between the antiphospholipid syndrome and the risk of bilateral adrenal infarction in non-COVID-19 patients as a potential mechanism [43][44][45][46].…”
Section: Adrenal Glandmentioning
confidence: 96%
“…COVID-19 is associated with an increased rate of pulmonary or extrapulmonary thrombotic complications [ 29 ], and adrenal injury may also occur through bilateral adrenal non-hemorrhagic or hemorrhagic infarction. Although incidental computed tomography (CT) findings compatible with adrenal infarction have been reported in 23% of patients with severe COVID-19 [ 30 ], the vast majority with bilateral involvement, clinically relevant cases are sparse with only nine reported so far [ 31 ]. Of note, two of these cases had positive antiphospholipid antibodies prior to COVID-19 diagnosis, suggesting a link between the presence of antiphospholipid syndrome and the risk of bilateral adrenal infarction [ 31 ].…”
Section: Pituitary–adrenal Responses In Covid-19 Patientsmentioning
confidence: 99%